Pengembangan Buku Suplemen Teks Fabel dalam Meningkatkan Pemahaman Nilai Antikorupsi Siswa SMP Kelas VII - Andi Prastiyo; Setya Yuwana Sudikan; Suyatno Suyatno (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this study was to produce a description of 1) the process of developing a fable text supplement book for understanding the anti-corruption values ​​of seventh grade junior high school students, 2) the quality of fable text supplement book development for understanding the anti-corruption value of seventh grade junior high school students as measured by the validity and practicality of the supplement book. This study was designed using development research methods. The supplement book development procedure uses a 4-D development model. The process of developing this supplement book model consists of four stages, namely definition, design, development, and distribution. The data collection techniques used were literature study and observation. Literature study is used to obtain written basics and opinions so that secondary data is obtained which will be used as a basis for comparison between theory and practice in the field. Observation is used to see the implementation of the development process including definition, design and development. The results showed that the fable text supplement book was appropriate because it could improve students' understanding of the anti-corruption values. This is evidenced by the quality of the fable text supplement book that is valid, practical, and effectively used. Details of practicality, namely the results of the implementation of the learning implementation plan of 80.1% in the good category, the results of the teacher's response to 81.3% in the good category, and the results of the student's response by 85.7% in the very good category. Then, the level of effectiveness of the fable text supplement book was categorized as very good. Details of the effectiveness, namely the results of teacher activity by 88.4% in the very good category, the results of student activity by 85.7% in the very good category, and the results of learning completeness by 99% in the very good category.